Single nucleotide polymorphisms in the bovine genome are associated with the number of oocytes collected during ovum pick up - Santos-Biase, W. K. F.; Biase, F. H.; Buratini, J. [UNESP]; Balieiro, J.; Watanabe, Y. F.; Accorsi, M. F. [UNESP]; Ferreira, C. R.; Stranieri, P.; Caetano, A. R.; Meirelles, F. V. (Elsevier B.V., 2012)
The number of follicles recruited in each estrous cycle has gained practical importance in artificial reproductive technology, as it determines the oocyte yield from ultrasound-guided ovum pickup for in vitro embryo production. We aimed to identify single nucleotide polymorphisms (SNPs) in bovine genes related to reproductive physiology and evaluate the association between the candidate SNPs and the number of oocytes collected from ultrasound-guided ovum pickup. We sequenced genomic segments of GDF9, FGF8, FGF10 and BMPR2 and identified seventeen SNPs in the Bos taurus and Bos indicus breeds. Two SNPs cause amino acid changes in the proteins GDF9 and FGF8. Three SNPs in GDF9, FGF8 and BMPR2 were genotyped in 217 Nelore cows (B. indicus), while two previously identified mutations in LHCGR and mitochondrial DNA (mtDNA) were genotyped in the same group. The polymorphisms in GDF9, FGF8, BMRP2 and LHCGR were significantly associated (P < 0.01) with the number of oocytes collected by ovum pickup, whereas the SNP in the mtDNA was not. In addition, we estimated an allelic substitution effect of 1.13 +/- 0.01 (P < 0.01) oocytes for the SNP in the FGF8 gene. The results we report herein provide further evidence to support the hypothesis that genetic variability is an important component of the number of antral follicles in the bovine ovary. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Folliculogenesis; Genetic marker; Embryo; In vitro fertilization